Strategi meningkatkan hubungan interpersonal dalam talian dalam kalangan remaja Malaysia - Bolong, Jusang; Tamam, Ezhar; Hassan, Md. Salleh; Abu Hasan, Musa (Department of Media Studies, Faculty of Arts & Social Sciences, University of Malaya, 2010)
The strategies used by the IRC (Internet Relay Chat) users will determine their level of interpersonal relations in computer-mediated communication. However, the strategies in building relationships between men and women are different. Therefore, this quantitative survey enumerates the different strategies used in improving interpersonal online relationship among teenagers. In-depth interview also has been used in this study to identify the strategies used in building interpersonal relationships through computer-mediated communication. Multi-regression tests are used to analyze the data.